Nano-chemistry and Bio-conjugation with perspectives on the design of Nano-Immune platforms, vaccines and new combinatorial treatments - Luna R Gomez Palacios; Sofia Martinez; Cecilia Tettamanti; Daniela Quinteros; A Guillermo Bracamonte (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
This Mini-Review and Opinion letter, it was addressed different themes and topics implicated in the development of new treatments and vaccines applied to pathologies developed in humans such as by Virus and related pathogens. In this context, it was presented and discussed different strategies used, which were contemplated from the design of small molecules, towards higher sized chemical structures and new Nanoarchitectures. In particular, it was discussed varied studies developed for the Corona Virus treatment; which afforded to the main mechanisms of action of pharmacophores and targeted functional Nanoparticles. In this direction, it was highlighted the importance of Bioconjugation of molecules and variable Nanoarchitectures for their incorporation within cells as well as for the development of Nano-vaccines. Moreover, it was discussed about the development of combinatory treatments based on different strategies recently reported. Similarly, it was presented different studies and developments actually in progress related to the design of functional and Multifunctional Nano-platforms with potential perspectives on Lab-On particles and Nano-vaccines for precision Nanomedicine and new treatments.